Meningkatkan Kompetensi Guru Dalam Strategi Pembelajaran Kolaboratif Untuk Menciptakan Lingkungan Belajar Ramah Anak, Gender, dan Difabel: Penelitian di SLBN B Tingkat Provinsi Kab. Sumedang - Imas Masruroh; Aang Mahyani; Siti Romlah; Nurhayati Nurhayati; Fitri Amira (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
Child-friendly, gender-responsive, and disability-conscious inclusive education is an important aspect of creating a fair and equitable learning environment. However, many educators still face challenges in implementing collaborative learning strategies that can embrace all students, including those with special needs and from diverse gender backgrounds. Therefore, this study was conducted at the provincial-level SLBN B in Sumedang Regency to enhance teachers' competence in implementing inclusive and empowering collaborative learning strategies. This study aims to strengthen teachers' capacity to create a learning environment that supports the social, emotional, and academic development of students with special needs, as well as to ensure a safe and inclusive setting. The activity is designed to assess educators' needs and identify challenges faced in implementing collaborative learning. Evaluation is conducted through measuring improvements in teachers' skills and changes in their attitudes towards students with special needs. The research approach uses the R&D method with the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. This model is chosen because it effectively facilitates the systematic and practical process of designing, developing, and evaluating teacher training programs. The methods used include direct training, collaborative learning simulations, and continuous mentoring to ensure consistent application of strategies. The data collected will be analyzed qualitatively to understand changes in teachers' perceptions and abilities in creating a more inclusive learning environment. The expected outcome of this research is an increase in teachers' competence in implementing collaborative learning, including their ability to build positive relationships with students, manage class dynamics inclusively, and create a learning atmosphere that encourages active participation. Thus, this study is expected to serve as a model for developing more inclusive and sustainable educational strategies at the provincial level SLBN B and other similar schools.